New paleomagnetic data from Late Neoproterozoic sedimentary successions in Southern Urals, Russia: implications for the Late Neoproterozoic paleogeography of the Iapetan realm - Lubnina, N.; Pisarevskiy, Sergei; Puchkov, V.; Kozlov, V.; Sergeeva, N. (Springer, 2014)
We present the results of paleomagnetic study of Ediacaran sedimentary successions from the Southern Urals. The analysis of the sedimentary rocks of the Krivaya Luka, Kurgashlya and Bakeevo Formations reveal stable mid-temperature and high-temperature remanence components.Mid-temperature components were acquired during Devonian (Bakeevo Formation) and Late Carboniferous–Early Permian remagnetization events. The high-temperature components in Kurgashlya and Bakeevo Formations are interpreted to be primar , because they are supported by a positive conglomerate test (Bakeevo Formation) and magnetostratigraphic pattern (Kurgashlya Formation). Thehigh-temperature component in the Krivaya Luka Formation is interpreted to be a Late Ediacaran overprint. Our new paleomagnetic poles together with some previously published Ediacaran poles from Baltica and Laurentia are used herein to produce a series of paleogeographic reconstructions of the opening of the Iapetus Ocean.